1984
DOI: 10.7164/antibiotics.37.706
|View full text |Cite
|
Sign up to set email alerts
|

A new antitumor antibiotic, kazusamycin.

Abstract: A new antibiotic kazusamycin, was isolated from the culture broth of Streptomryces sp. No. 81-484, which shows antitumor activity against experimental marine tumors. This antibiotic did not possess antibacterial activity against Gram-positive and Gramnegative bacteria, but showed strong cytotoxic activity against HeLa cells in vitro. The chemical and physico-chemical properties of kazusamycin suggest that the molecular formula of this antibiotic is C;H,,O, (MW 556). In the course of a continuing search for nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Kazusamycin A (142) was active against fungi and some yeasts, but was inactive against Gram-positive and Gram-negative bacteria. 234 The antimicrobial spectrum of kazusamycin B (143) is similar to that of kazusamycin A. 235 The mode of action of leptomycin B (147) with Schizosaccharomyces pombe was examined.228 Low concentrations caused inhibition of cell division, leading to the production of elongated cells with morphologically altered nuclei.…”
Section: The Leptomycins Kazusamycins and Anguinomycinsmentioning
confidence: 99%
“…Kazusamycin A (142) was active against fungi and some yeasts, but was inactive against Gram-positive and Gram-negative bacteria. 234 The antimicrobial spectrum of kazusamycin B (143) is similar to that of kazusamycin A. 235 The mode of action of leptomycin B (147) with Schizosaccharomyces pombe was examined.228 Low concentrations caused inhibition of cell division, leading to the production of elongated cells with morphologically altered nuclei.…”
Section: The Leptomycins Kazusamycins and Anguinomycinsmentioning
confidence: 99%
“…Finally, appropriate functional group manipulation, including chemodifferentiation of prim -, sec -, and allylic alcohol completed the total synthesis of kazusamycin A, whose spectroscopic data ( 1 H NMR, 13 CNMR, IR, HRMS) were in complete agreement with that of the natural kazusamycin A. The synthetic sample showed negative optical rotation ([α] 27 D −87.7°, c 0.358, MeOH) in accordance with the natural compound ([α] 20 D −83.5°, c 0.1, MeOH) . This fact indicates that the natural kazusamycin A has the absolute configuration shown in Figure .…”
mentioning
confidence: 71%
“…Kazusamycin A, isolated from the culture broth of an actinomycete strain, 81-484, has been found to exhibit potent antitumor activity on P388 leukemia and sarcoma 180, as well as anitimicrobial activity . It was also effective in completely preventing growth of HeLa cells at a concentration of 3.3 ng/mL .…”
mentioning
confidence: 99%
“…The higher molecular weight natural delta-lactones, such as camptothecin (Wani et al, 1980) and kazusamycin (Umezawa et al, 1984) have been reported to show antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, delta-lactones (DLs) produced from plants or fungi, such as camptothecin (Wani et al, 1980;Xu and Ling, 1985), kazusamycin (Umezawa et al, 1984) and sultriecin (Ohkuma et al, 1992), have been studied for their antitumor activity.…”
Section: Introductionmentioning
confidence: 99%